EFFECTIVENESS OF THE ADMINISTRATIVE SERVICES OF THE SIDOARJO PUBLIC SERVICE SYSTEM (SIPRAJA) IN HANDLING DIGITAL-BASED CORRESPONDENCE FOR VILLAGE COMMUNITIES - Azzahra, Naura Salsabila Neisya; Agustina, Isna Fitria (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to analyze and describe the effectiveness of the Sidoarjo Public Service System (SIPRAJA) in improving the quality of administrative services, particularly correspondence at the village level, specifically in Larangan Village, Candi District, Sidoarjo Regency. Method: The approach used is a qualitative method with descriptive data collection through interviews, observations, and literature studies, with success indicators based on Sutrisno's theory of effectiveness, including program understanding, target accuracy, timeliness, achievement of objectives, and real change. Results: The results of the study show that SIPRAJA is generally effective in accelerating administrative processes and facilitating access to community services, as well as providing direct benefits and positive changes in public services. However, there are obstacles such as low digital literacy, which affects the level of understanding and use of this system. Novelty: The focus of this research lies in its specific focus on handling correspondence at the village level and in-depth analysis based on comprehensive effectiveness indicators. The conclusion shows that although SIPRAJA has been running effectively, increased socialization and digital education are urgently needed so that its benefits can be felt more evenly and optimally.